Abrahamic descent, testamentary adoption, and the law in Galatians : differentiating Abraham's sons, seed, and children of promise - Trick, Bradley R., 1975- (Novum Testamentum, Supplements, 2016)
In this volume, Bradley R. Trick argues that Hellenistic testamentary adoption provides the key to understanding Abrahamic descent and its implications for the law in Galatians. By thoroughly analyzing the Greco-Roman and Jewish contexts of Paul's references to testaments/covenants (διαθῆκαι) and adoption, Trick establishes that Gal 3-4 portrays the Abrahamic διαθήκη as a Hellenistic testament through which God adopts Abraham. This insight enables a coherent and collectively consistent interpretation of Paul's Abrahamic appeals to emerge, one in which "sons" (3:7) designates Jews, "children of promise" (4:28) designates gentiles, and "seed" designates Christ (3:16) and the interdependent union of Jews and gentiles in Christ (3:29). The need to preserve the singularity of this seed then grounds God's giving of the law.